A mammalian system for high-resolution imaging of intact cells by cryo-electron tomography. (March 2021) - Li, Xia; Park, Donghyun; Chang, Yunjie; Radhakrishnan, Abhijith; Wu, Hangjun; Wang, Pei; Liu, Jun
Abstract: Mammalian cells contain an elaborate network of organelles and molecular machines that orchestrate essential cellular processes. Visualization of this network at a molecular level is vital for understanding these cellular processes. Here we present a model system based on nerve growth factor (NGF)-differentiated PC12 cells (PC12 + ) and suitable for high resolution imaging of organelles and molecular machines in situ . We detail an optimized imaging pipeline that effectively combines correlative light and electron microscopy (CLEM), cryo-focused ion beam (cryo-FIB), cryo-electron tomography (cryo-ET), and sub-tomogram averaging to produce three-dimensional and molecular resolution snapshots of organelles and molecular machines in near-native cellular environments. Our studies demonstrate that cryo-ET imaging of PC12 + systems provides an accessible and highly efficient avenue for dissecting specific cellular processes in mammalian cells at high resolution.